2017
DOI: 10.2147/ijnrd.s126844
|View full text |Cite
|
Sign up to set email alerts
|

Optimal management of primary focal segmental glomerulosclerosis in adults

Abstract: Focal segmental glomerulosclerosis (FSGS) is a frequent glomerular kidney disease that is revealed by proteinuria or even nephrotic syndrome. A diagnosis can be established from a kidney biopsy that shows focal and segmental glomerulosclerosis. This histopathological lesion may be caused by a primary podocyte injury (idiopathic FSGS) but is also associated with other pathologies (secondary FSGS). The first-line treatment for idiopathic FSGS with nephrotic syndrome is a prolonged course of corticosteroids. Howe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0
3

Year Published

2018
2018
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 100 publications
0
25
0
3
Order By: Relevance
“…Some retrospective studies have suggested that steroid and alkylating agents, such as chlorambucil, can favor remission of FSGS [34,35]. Alkylating agents are associated with higher remission rates and a longer time of remission than calcinuurin inhibitors [36], and the high costs of tacrolimus treatment may be less effective in patients with FSGS than other types, such as minimal change nephropathy [32].…”
Section: Discussionmentioning
confidence: 99%
“…Some retrospective studies have suggested that steroid and alkylating agents, such as chlorambucil, can favor remission of FSGS [34,35]. Alkylating agents are associated with higher remission rates and a longer time of remission than calcinuurin inhibitors [36], and the high costs of tacrolimus treatment may be less effective in patients with FSGS than other types, such as minimal change nephropathy [32].…”
Section: Discussionmentioning
confidence: 99%
“…In steroid resistant, steroid-dependent or steroid-contraindicated patients, other immunosuppressive therapies are suggested 46 . Adverse effects of the long-term use of such toxic and "non-specific" therapies have led to a demand for more selective immunomodulating and immunosuppressive regimens 47,48 .…”
Section: Adultsmentioning
confidence: 99%
“…Clinically, FSGS is often associated with nephrotic syndrome, which is characterized by proteinuria of > 1 g/ m 2 /24 h, hypoalbuminemia, generalized edema, and hyperlipidemia 5,6 . The other clinical presentations of FSGS are hypertension, microscopic hematuria, renal failure, and serum creatinine increment 7 . The first-line treatment strategy for FSGS is oral corticosteroids, although it still seems to be far from satisfactory and remains a challenge for nephrologists 7 .…”
Section: Introductionmentioning
confidence: 99%
“…The other clinical presentations of FSGS are hypertension, microscopic hematuria, renal failure, and serum creatinine increment 7 . The first-line treatment strategy for FSGS is oral corticosteroids, although it still seems to be far from satisfactory and remains a challenge for nephrologists 7 . The rate of spontaneous remission in this glomerular disease is <5%, whereas a complete or partial remission with steroid therapy occurs in 40-60% of cases 7,8 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation